PENGARUH STRATEGI BAURAN PEMASARAN TERHADAP KEPUTUSAN MAHASISWA MEMILIH UNIVERSITAS KATOLIK WIDYA MANDALA MADIUN - Kurniawati, Dyah (Widya Warta, 2013)
Higher learning institute is an option to get the highest formal education. The selection of higher learning institute and department becomes the focus for prospective students. The strategy of marketing mix services should be considered by the higher learning institute so as to steer prospective students in choosing their study place. The sample of this study was students of Catholic University of Widya Mandala Madiun in the academic year 2011/2012. The results of the research showed that marketing mix services comprising product, price, promotion, place, people, process and service simultaneously have an influence on the students’ decision. Partially, there is no influence of product, place, process, and service to the students’ decision, while price/cost of education, promotion, and people do not influence the students’ choice University leaders should pay attention to the elements of the marketing mix and focus on students, because students are potential resources as well as a potential marketing power. They are the source of information and do not demand payment for efforts.